Severe cutaneous drug toxicity following disitamab vedotin treatment for metastatic gastric cancer: a case report - Zhao Luping; Cheng Zhen; Li Piaopiao (Frontiers in Oncology)
BackgroundThis study reports a case of severe cutaneous toxicity in a patient with metastatic gastric cancer induced by disitamab vedotin, emphasizing the need for careful monitoring and management in such treatments.Case presentationA 71-year-old female was admitted to hospital complaining of serious rashes following the first cycle of disitamab vedotin regimen for metastatic gastric cancer. The doctor diagnosedtoxic epidermal necrolysis (TEN) induced by the drug. The patient received high-dose methylprednisolone due to the side effects. This resulted in a gradual improvement of symptoms.ConclusionDuring the use of disitamab vedotin, patients need to be monitored for severe skin toxicity.